Psychologické aspekty manažerské profese - Matysová, Kamila; Filipová, Alena, 1965-; Zeman, Jiří; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
The following paper attempts to offer a framework for explaining relations between manager profession and psychological aspects of human being. Nowadays the competition is increasing and knowledge of psychology and communication theories is becoming a crucial competitive edge. The work is intended to support importance of psychology for management and business. The author seeks inspiration both in depth psychology and in humanistic and phenomenological theories. In the first step, the author offer viewpoint of leadership and style of business communication as a consequence of human aggression and temperament qualities. The author draws the conclusion on the basis of own research. In the second step, the author tries to outline the complex analysis of human communication in compliance with business situations. Finally, the author compares coaching and therapeutic methods. The thesis presents scheme of recommendations for managers and businessmen.
Vedoucí práce: Alena Filipová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses